Absenteísmo à consulta odontológica de crianças com até 5 anos: o caso de Belo Horizonte - Taiomara Vieira Mania (2017)
Epidemiological surveys have revealed a high prevalence of caries among children aged 5 years in Brazil, as well as the populations high no-show rate at dental appointments scheduled in the public health system. Objective: To identify the reasons for nonattendance at dental appointments scheduled in the public health system among children aged up to 5 years. Methodology: Following a qualitative methodology, at least two mothers or caregivers of patients who missed dental appointments from each administrative region of Belo Horizonte MG, Brazil, for a total of 18 mothers, were interviewed. Interviews followed a semistructured script, were audio recorded, and were transcribed in full. Data were read, classified into themes, and subjected to content analysis. Results: Interviews showed that caregivers, although perceiving their childrens need for dental care, struggle to fulfill scheduled appointments because they cannot be available to accompany the children (e.g., due to lack of time off from work). Some interviewees reported forgetting appointments due to the lengthy lapse between the scheduling and appointment dates, whereas others attributed nonattendance to childrens illness on the day of the appointments. Interviews also revealed miscommunication between the social actors involved, as confirmed by reports of their lack of knowledge about the scheduled appointments. Conclusion: Empowerment-focused caregivers counseling is necessary in planning oral health promotion strategies for children aged 5 years or less. Interventions in the scheduling system (e.g., offering appointment reminders or alternative appointment times in health units) could also benefit their use of the service.